Investigating the Role of Stress-Preventive Leadership in the Workplace Hospital: The Cross-Sectional Determination of Relational Quality by Transformational Leadership - Stuber, Felicitas; Seifried-Dübon, Tanja; Rieger, Monika A.; , Contributors of the SEEGEN Consortium; Zipfel, Stephan; Gündel, Harald; Junne, Florian; Rothermund, Eva; Mulfinger, Nadine; Jarczok, Mark; Angerer, Peter; Maatouk, Imad; et al. (Frontiers in Psychiatry, 2019)
Introduction: A good relationship quality between leaders and staff members promotes mental health and prevents stress. To improve the relationship quality, it is important to identify variables which determine relationship quality at the workplace. Therefore, this study aims to identify specific leadership characteristics which support the development of a positive relationship between hospital leaders and staff members. Methods: A cross-sectional study design was applied. A total number of 1,137 leaders (n = 315) and staff members (n = 822) of different professions (physicians, nursing staff, therapeutic professionals, administration staff, IT staff, clinical services, office assistants, scientists, others) working at a tertiary hospital in Germany assessed transformational leadership style as a staff-oriented leadership style and leader–member relationship quality by self-report questionnaires [integrative leadership questionnaire (FIF), leader–member exchange (LMX-7) questionnaire]. The data were statistically analyzed by mean comparisons and a multiple linear regression analysis. Results: Leaders rated their own transformational leadership style (M = 3.98, SD = 0.43) systematically higher than staff members assessed their leader (M = 2.86, SD = 1.04). Evaluation of relationship quality showed similar results: leaders evaluated their relationship quality to one exemplary staff member higher (M = 4.06, SD = 0.41) than staff members rated their relationship quality to their direct leader (M = 3.15, SD = 0.97). From the staff members’ perspective, four sub-dimensions of transformational leadership, that is, “individuality focus,” “being a role model,” “fostering innovations,” and “providing a vision” showed large effect sizes in the regression analysis of relationship quality (R2 = 0.79, F (14,690) = 189.26, p < 0.001, f = 1.94). Discussion: The results of our study are in line with previous investigations in other working contexts and point to a profession-independent association as the professional group of participants did not contribute to the variance explanation of the regression analysis. The exploration of potential determinants of relationship quality at work can, for example, support the development of leadership training programs with a focus on transformational leadership style. This might be an opportunity to foster high relationship quality between leaders and staff members and consequently might represent one strategy to prevent stress in the health care sector.